Postmilitary Adjustment to Civilian Life: Potential Risks and Protective Factors. Issue 8 (1st August 2014) - MacLean, Mary Beth; Van Til, Linda; Thompson, James M.; Sweet, Jill; Poirier, Alain; Sudom, Kerry; Pedlar, David J.
Abstract : Background: Adjustment to civilian life in Canadian veterans after release from military service has not been well studied. Objectives: The objectives of this study were: (1) to explore dimensions of postmilitary adjustment to civilian life and (2) to identify demographic and military service characteristics associated with difficult adjustment. Design: Data were analyzed from a national sample of 3, 154 veterans released from the regular Canadian Forces during 1998 to 2007 in a cross-sectional survey conducted in 2010 called the Survey on Transition to Civilian Life. Methods: The prevalence of difficult adjustment to civilian life for selected characteristics was analyzed descriptively, and confidence intervals were calculated at the 95% level. Multivariable logistic regression analysis was used to identify characteristics available at the time of release that were associated with difficult adjustment. Results: The prevalence of difficult adjustment to civilian life was 25%. Statistically significant differences were found across indicators of health, disability, and determinants of health. In multivariable regression, lower rank and medical, involuntary, mid-career, and Army release were associated with difficult adjustment, whereas sex, marital status, and number of deployments were not. Limitations: Findings cannot be generalized to all veterans because many characteristics were self-reported, important characteristics may have been omitted, and causality and association among health, disability, and determinants of health characteristics could not be determined. Conclusions: Postmilitary adjustment to civilian life appears to be multidimensional, suggesting the need for multidisciplinary collaboration between physical therapists and other service providers to mitigate difficult transition. Potential risk and protective factors were identified that can inform interventions, outreach strategies, and screening activities, as well as further research.